Epigenetic silencing of DNA sensing pathway by FOXM1 blocks stress ligand-dependent antitumor immunity and immune memory - Santosh Timilsina; Jian Yu Huang; Nourhan Abdelfattah; Daisy Medina; Deepika Singh; Shahad Abdulsahib; Panneerdoss Subbarayalu; Trong Phat Do; Prabhakar Pitta Venkata; Saif Nirzhor; Jack Prochnau; Mukund Bhandari; et al. (Nature Communications)
Abstract The interplay between tumor cells and the microenvironment significantly influences cancer progression. Here, we report a significant role of the transcription factor FOXM1 in shaping the tumor immune landscape. Single-cell sequencing reveals that tumor-intrinsic FOXM1 creates an immune-suppressive tumor microenvironment by inhibiting expression of stress ligands (including ULBP1) on cancer cells, thereby blocking NKG2D-NKG2DL interactions critical for priming natural killer- and T cell-mediated cytotoxicity of cancer cells. FOXM1 suppresses ULBP1 expression by epigenetically silencing the DNA-sensing protein STING using a DNMT1-UHRF1 complex, which in turn inhibits the unfolded protein response protein CHOP from activating ULBP1. Importantly, cancer patients with higher levels of FOXM1 and DNMT1, and lower levels of STING and ULBP1, have worse survival and are less responsive to immunotherapy. Collectively, our findings provide key insight into how a tumor-intrinsic transcription factor epigenetically shapes the tumor immune microenvironment, with strong implications for refining existing and designing new cancer immunotherapies.